2011
DOI: 10.1523/jneurosci.4637-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Information Capacity and Transmission Are Maximized in Balanced Cortical Networks with Neuronal Avalanches

Abstract: The repertoire of neural activity patterns that a cortical network can produce constrains the ability of the network to transfer and process information. Here, we measured activity patterns obtained from multisite local field potential recordings in cortex cultures, urethaneanesthetized rats, and awake macaque monkeys. First, we quantified the information capacity of the pattern repertoire of ongoing and stimulus-evoked activity using Shannon entropy. Next, we quantified the efficacy of information transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
575
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(616 citation statements)
references
References 43 publications
37
575
2
2
Order By: Relevance
“…Although it may be good for epilepsy patients to have a lower R value corresponding to a lower excitability to prevent the likelihood of seizures, the concomitant decrease in the variability of synchronization might be disadvantageous for optimal brain network functioning. Previous studies using in vitro preparations have shown that the IEMs similar to the ones used here are closely related to certain capabilities in information processing (41)(42)(43)(44). IEMs could therefore be potential candidates to quantify the neural correlates of such cognitive deficits in humans.…”
Section: Discussionmentioning
confidence: 72%
“…Although it may be good for epilepsy patients to have a lower R value corresponding to a lower excitability to prevent the likelihood of seizures, the concomitant decrease in the variability of synchronization might be disadvantageous for optimal brain network functioning. Previous studies using in vitro preparations have shown that the IEMs similar to the ones used here are closely related to certain capabilities in information processing (41)(42)(43)(44). IEMs could therefore be potential candidates to quantify the neural correlates of such cognitive deficits in humans.…”
Section: Discussionmentioning
confidence: 72%
“…To address this question, we investigated a parsimonious model network of probabilistic integrate-and-fire neurons with all-to-all connectivity 6,19,20 (Fig. 2a).…”
Section: And Supplementary Information 5)mentioning
confidence: 99%
“…Previous computational studies and cortex slice experiments suggest that the critical regime optimizes several aspects of information processing (reviewed in ref. 3), including dynamic range 20,26,28 and information transmission 5,6 . Our observation that transient response to stimulus onset is not critical suggests that sensory cortex dynamically adapts to gain the functional benefits of critical dynamics during strong sensory input.…”
mentioning
confidence: 99%
“…Greater dynamic range is important for the adaptability and efficiency of neural systems because it allows a greater range of response to a greater range of stimuli. Interestingly, cellular research indicates that dynamic range (and information transfer within networks) is best achieved when cellular excitation and inhibition are balanced, and response variability is optimally high; upon imbalance and a lack of response variability, dynamic range suffers (Shew et al 2009;Shew et al 2011). In the present case, our young and fast performers appeared to exhibit the greatest dynamic range of BOLD signal (i.e., greater signal variability), within and across voxels and when making transitions from rest to task.…”
Section: Why An Increase In Brain Variability During Internal-to-extementioning
confidence: 99%